Uncertainty and Public Investment Multipliers : The Role of Economic Confidence - Gbohoui, William (IMF Working Papers; Working Paper ;, 2021)
This paper investigates how macroeconomic uncertainty affects the fiscal multiplier of public investment. In theory, uncertainty can reduce the multiplier if the private sector becomes more cautious and does not respond to the fiscal stimulus. Conversely, it can increase the fiscal multiplier if public investment shocks improve private agents' expectations about future economic outlook, and lead to larger private spending. Using the disagreement about GDP forecasts as a proxy for uncertainty, we find that unexpected increases in public investment have larger and longer-lasting effects on output, investment, and employment during periods of high uncertainty, with multipliers above 2, and the larger multipliers are not driven by economic slack. Public investment shocks are also found to boost private sector confidence during heightened uncertainty, driving-up expectations about future economic development which in turn magnify private sector response to the initial stimulus.